Imaging pearls of the annular pancreas on antenatal scan and its diagnostic dilemma: A case report - Pradeep Kumar Roul; Ashish Kaushik; Manish Kumar Gupta; Poonam Sherwani (EL-Med-Pub, 2020)
Background: Annular pancreas is an uncommon cause of duodenal obstruction and rarely causes complete duodenal obstruction. Due to its rarity of identification in the antenatal period and overlapping imaging features with other causes of duodenal obstruction; it is often misdiagnosed. Case presentation: A 33-year-old primigravida came for routine antenatal ultrasonography at 28 weeks and 4 days of gestational age. On antenatal ultrasonography, dilated duodenum and stomach were seen giving a double bubble sign and a hyperechoic band surrounding the duodenum. Associated polyhydramnios was also present. Fetal MRI was also done. Postpartum ultrasonography demonstrated pancreatic tissue surrounding the duodenum. The upper gastrointestinal contrast study showed a non-passage of contrast beyond the second part of the duodenum. Due to symptoms of obstruction, the neonate was operated on, and the underlying cause was found to be the annular pancreas. Conclusion: Diagnosis of duodenal obstruction due to the annular pancreas is very important in the antenatal period to plan for appropriate therapeutic interventions after birth. A double bubble sign is seen due to various etiologies however the presence of a hyperechoic band in the antenatal ultrasound may point to the diagnosis of the annular pancreas.